Evaluation of quality of care in health services for survivors of sexual violence (Research, Society and Development, 2020)
The objective of this systematic review was to identify which positive and negative indicators are present in scientific articles on the evaluation of care in health services for survivors of sexual violence. The research was carried out in the electronic database MEDLINE, with the descriptors "Sexual Violence", "Sexual Abuse" and "Health Services". Fifteen empirical studies were found, carried out in 12 countries and published in the period from 2002 to 2020. The results revealed as positive indicators: humanized treatment; believing the testimony of the victims; receive information about procedures; having the option to choose interventions; adequate staff training; having a mental health service; secrecy and privacy; have adequate infrastructure; and resoluteness. And as negative indicators: non-humanized care; not believing the testimony of the victims; not receiving information about the procedures; not having the option to choose; lack of adequate staff training; improve mental health services; absence of secrecy and privacy; absence of supplies; ignorance of health professionals about sexual violence in people of the male gender; absence of specific protocols; more clearly define the roles and responsibilities of health professionals and forensic specialists; absence of discipline on sexual violence in undergraduate courses in health; access problems due to lack of information about these services; and access problems due to the stigma and silence surrounding people in situations of sexual violence. These indicators are expected to provide subsidies for the improvement of public policies.